Geo-genetics patterns in Bambara groundnut: investigating the role of geography in the distribution of genetic variation - Santos, Roberto (2018)
The study of the geo-genetic structure of human-associated plant species can help us to understand the ways that the landscape, environment, and socio-cultural factors influence these populations. This research project aims to identify spatial-related factors (distance, environment, culture) that affect the genetic structure of Bambara groundnut, an underutilised crop mainly cultivated in sub-Saharan Africa. I used a genetic database of 33 landraces of Bambara groundnut, 128 samples in total, genotyped using 19 microsatellite markers. I tested for the presence of genetic structure and genetic barriers using allele frequencies, ordination, and clustering analyses. Next, I explored how geographic distance, environment, and human-mediated dispersal influence genetic diversity by investigating the relationship between four measures of dissimilarity. I analysed these relationships using Mantel tests and structural equation modelling (SEM). Finally, I examined the relationship between genetic variation and soil water content using Moran's I statistics and generalised least squares (GLS) regression analyses. I found genetic structure among different landraces. The clustering analyses result indicated strong differentiation between landraces populations, with clusters mainly associating landraces to their geographic origins. The SEM results suggested that genetic similarity among landraces of Bambara is related to geographic proximity and, to a lesser extent, linguistic similarity between human communities. There was no relationship between genetic similarity and environmental differences. I also discussed the challenges and possible solutions for integrating distinct discipline-datasets. Overall, this thesis highlighted the importance of cultural aspects and social networks in the genetic structure of human-associated plant species.